2011
DOI: 10.1055/s-0031-1283188
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Injuries in French Professional Soccer Players

Abstract: In this prevalence cohort study, injuries sustained during 15 seasons in a professional soccer team were investigated according to the different soccer seasons, number of matches per season, month the injury occurred, location, severity, playing position and the team's rank at the end of the French professional championship. Altogether, 903 injuries in 173 professional soccer players were reported. Injury incidence per 1 000 h of exposure during matches and training was 4.7±5. This incidence did not vary signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
69
5
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 17 publications
12
69
5
11
Order By: Relevance
“…Finally, our data showed significant differences in injury incidence depending on the phase of the season, as previous studies have found (Dauty & Collon, 2011;Ekstrand et al, 2011b;Hawkins et al, 2001;Morgan & Oberlander, 2001;Walden et al, 2005b;Woods et al, 2002). In the present study, the highest incidence of training injuries was observed during the pre-season, most likely because of inadequate recovery between seasons and/or inappropriate demands during the pre-season.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Finally, our data showed significant differences in injury incidence depending on the phase of the season, as previous studies have found (Dauty & Collon, 2011;Ekstrand et al, 2011b;Hawkins et al, 2001;Morgan & Oberlander, 2001;Walden et al, 2005b;Woods et al, 2002). In the present study, the highest incidence of training injuries was observed during the pre-season, most likely because of inadequate recovery between seasons and/or inappropriate demands during the pre-season.…”
Section: Discussionsupporting
confidence: 72%
“…Recent European (Dauty & Collon, 2011;Ekstrand, Hagglund, & Walden, 2011b;Hagglund, Walden, & Ekstrand, 2005) and American (Morgan & Oberlander, 2001) epidemiological studies of professional male football players reported an overall incidence of approximately 6-8 injuries per 1000 h of exposure. Previous studies have shown that football injuries mainly affected the lower extremities (Wong & Hong, 2005), particularly the ankle, knee or thigh (Azubuike & Okojie, 2009;Ekstrand, Hagglund, & Walden, 2011a;Junge & Dvorak, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We found several studies which support these findings [4,20,[42][43][44][45]. We believe that this finding may be explained by extrinsic factors, such as the characteristics of the playing terrain, as soccer is practiced on changing surfaces due to the climate, the length of the grass, the amount of watering prior to the match, etc., and the length and shape of the studs or intrinsic factors such as a muscle imbalance with the knee extensor muscles.…”
Section: Discussionsupporting
confidence: 59%
“…Within the joint injuries, the ankle sprains affecting the lateral collateral ligament were the most frequent. In the literature reviewed we have found a number of studies that identify joint injuries as the second most frequent after muscle injuries [4,5,16,22,27,46,[34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Thus, we can affirm that joint injuries are the second most frequent after muscle injuries.…”
Section: Discussionmentioning
confidence: 89%
“…Injury occurrence notably, results in decreased player availability and subsequent non-participation in match-play potentially impacts on team performance although contradictory observations exist (Árnason et al, 2004;Dauty & Collon, 2011;Eirale, Tol, Farooq, Smiley, & Chalabi, 2013;Hägglund et al 2013). The association between squad management, player availability and injury and success in professional soccer therefore warrants further attention.…”
Section: Introductionmentioning
confidence: 99%